Cultural Placemaking to Preserve Suku Laut Heritage in Indonesia’s Riau Islands Communities - Suwarlan, Stivani Ayuning; Aguspriyanti, Carissa Dinar; Gunawan, I Gusti Ngurah Anom; Rosetia, Amanda; Manikam, Arti; Kellen; Lubis, Tari Wahyuni; Prakoso, Yoseph Seno (Departement of Architecture, Universitas Islam Indonesia, 2026)
This research explores efforts to preserve the cultural heritage of the Suku Laut in the Riau Islands through placemaking initiatives within coastal settlements. Historically dependent on the sea for their livelihood and identity, the community now faces significant challenges in maintaining their cultural traditions amidst modernization and shifts in coastal ecosystems. This research aims to identify design strategies that harmonize traditional cultural values with the demands of contemporary development, focusing on revitalizing the community’s living spaces. Employing qualitative methods, including interviews, field observations, and document analysis, the research highlights the critical role of cultural placemaking. Key elements include incorporating traditional architectural features, using locally sourced materials, and restoring communal spaces to promote sustainable coastal settlement designs. The findings indicate that this approach which respects the cultural values and the Suku Laut's relationship with their natural environment can promote social and environmental sustainability. In conclusion, integrating cultural placemaking into coastal settlement design is pivotal for preserving the cultural heritage and enhancing the quality of life for the Suku Laut amidst the ongoing modernization.